GEOMETRI DAN PERMASALAHAN DALAM PEMBELAJARANNYA (SUATU PENELITIAN META ANALISIS) - Budiarto, Mega Teguh; Artiono, Rudianto (Prodi Magister Pendidikan Matematika Pascasarjana Universitas Pattimura Ambon, 2019)
Geometry teaches us not only about how to give appreciation for something, but also how to find connections that occur between geometry material and other lecture material. In addition, geometry also trains communication through exploration, discussion, conjecture and investigation. The problems that exist in basic geometry skills in a row are problems related to logic skills, drawing skills, visual skills, verbal skills, and applied skills. Based on geometric learning using analytical presentation, the problem of using axiomatic deductive is at the top, then the problem of perception. Misconceptions about visual processes and activities, and finally problems with the use of procedures, concepts, and principles